Antibiogram and heavy metal resistance of pathogenic bacteria isolated from moribund cage cultured silver catfish (Pangasius sutchi) and red hybrid tilapia (Tilapia sp.) - Lee Seong Wei; Najiah Musa; Wendy Wee; Nadirah Musa (2010)
Antibiogram and heavy metal resistance patterns of pathogenic bacteria isolated from moribund cage cultured silver catfish (Pangasius sutchi) and red hybrid tilapia (Tilapia sp.) from Sungai Manir, Terengganu, Malaysia were studied and characterized. Sungai Manir is one of the famous rivers in Terengganu for its wide variety of cage cultured freshwater fish. However, to date, the baseline information of antibiogram and heavy metal resistance patterns of the pathogenic bacteria attacking the freshwater fish cultured in Sungai Manir is still lacking. Therefore, this study was carried out, which may be useful for fish farmers as a guideline for fish prophylactic and treatment purposes. Furthermore, present studies also provide information on the safety level of consuming freshwater fish produced from Sungai Manir. In the present study, bacteria were isolated from 100 fish of each moribund silver catfish and red hybrid tilapia using seven media including tryptic soy agar (TSA), Mac Conkey, thiosulphate citrate bile salt (TCBS), eosin methylene blue (EMB), glutamate starch pseudomonas (GSP), xylose lysine deoxycholate (XLD) and Baird Parker media. Identification of bacteria was carried out using conventional biochemical tests and confirmed by commercial bacterial identification kit. Antibiogram of the bacterial isolates against 18 antibiotics; oxolinic acid (2 μg), ampicillin (10 μg), erythromycin (15 μg), furazolidone (15 μg), lincomycin (15 μg), oleandomycin (15 μg), amoxicillin (25 μg), colistin sulphate (25 μg), sulphamethoxazole (25 μg), chloramphenicol (30 μg), doxycycline (30 μg), florfenicol (30 μg), flumequine (30 μg), kanamycin (30 μg), nalidixic acid (30 μg), tetracycline (30 μg), nitrofurantoin (50 μg) and spiramycin (100 μg) was carried out using disk diffusion method, whereas heavy metal resistance patterns (Hg2+, Cd2+, Cr6 + and Cu2+) of the bacterial isolates was determined through twofold agar dilution method. The results showed that the percentage of sensitivity case of the 120 bacterial isolates to the tested antibiotics was 62.7%. This was followed by resistance (26.9%) and intermediary sensitive (10.4%) cases. In terms of the heavy metal resistance patterns, all bacterial isolates were resistant to Hg2+ and Cr6 +. However, only 27.8% and 16.7% of the bacterial isolates were sensitive to Cu2+ and Cd2+, respectively. The multiple antibiotic resistance (MAR) indices indicated that the cage cultured silver catfish and red hybrid tilapia were under high exposure to the tested antibiotic. Overall, the results of the present studies showed that Sungai Manir may be polluted with heavy metal and antibiotic residues.